PENGGUNAAN PENDEKATAN SAINTIFIK BERBANTUAN MEDIA POPO KENAMBU UNTUK MENINGKATKAN HASIL BELAJAR DAN EKOLITERASI SISWA - Sartika, Santi; Kurnia, Dadang; Sunaengsih, Cucun (Jurnal Pena Ilmiah, 2019)
Problem in this research is result of study and student’s ecoliteration on theme 1, sub-theme 2 learning. It was aimed to get the increasing of the study result and ecoliteration of primary school student by using media help approach. It used class action research method which was done to 5th graders of SDN Mandalaherang II, Cimalaka Sub-district, Sumedang. The research target was 85% of study result reach 70 for its KKM and enhancement of student’s ecoliteration. The result of this research, from scientific approach by using popo kenambu media help, on cycle III percentage of teacher’s working plan and completely done in 100%, student who was reached the result was about 91,37%, and student’s ecoliteration on 81,52%. Thus it can be concluded that there was an enhancement of teacher’s working, study result, and student’s ecoliteration in using scientific approach of study within popo kenambu media help.